Precipitation variation: a key factor regulating plant diversity in semi-arid livestock grazing lands - Wu, Yantao; Li, Hao; Cui, Jiahe; Han, Ying; Li, Hangyu; Miao, Bailing; Tang, Yongkang; Li, Zhiyong; Zhang, Jinghui; Wang, Lixin; Liang, Cunzhu (Frontiers in Plant Science, 2024)
Livestock presence impacts plant biodiversity (species richness) in grassland ecosystems, yet extent and direction of grazing impacts on biodiversity vary greatly across inter-annual periods. To investigate the effects of grazing on biodiversity under different precipitation variability, an eight-year (2014-2021) sheep grazing gradient experiment had been conducted in a semi-arid grassland. In the semi-arid Stipa grassland, grazing by sheep did not have a direct impact on species richness. However, increased grazing indirectly enhanced species richness by elevating community dominance (increasing the sheltering effect of Stipa grass). Importantly, intensified grazing also regulates excessive community biomass resulting from increased inter-annual wetness (SPEI), amplifying the positive influence of annual humidity index on species richness. Lastly, we emphasize that, in water-constrained grassland ecosystems, intra-annual precipitation variability (PCI) was the most crucial factor driving species richness. We had found that the water-heat synchrony during the growing season, by releasing physiological constraints imposed by plants, significantly promoted species richness. Therefore, species richness is the outcome of multiple interacting factors. Our study provides strong evidence for how to regulate grazing intensity to increase biodiversity under future variable climate patterns. We suggest adapting grazing intensity according to local climate variability to achieve grassland biodiversity conservation.